2023
DOI: 10.3390/ma16175960
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Flexural Performance of Steel Pipe Steel Slag Powder Ultra-High-Performance Concrete Components

Xianyuan Tang,
Chenzhuo Feng,
Jin Chang
et al.

Abstract: In order to study the flexural performance of the combined structure of steel-pipe and steel slag powder ultra-high-performance concrete (UHPC), nine round steel-pipe beams filled with steel slag powder UHPC of different types were fabricated according to the orthogonal test method with the steel pipe type, coarse aggregate content, steel fiber admixture, and curing system as parameters. The broken ring morphology, deformation characteristics, deflection distribution, and flexural bearing capacity of the steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Yang et al evaluated the effect of the number of drains per pile and the orientation of the drains relative to the direction of shaking [17]. Tang et al studied the flexural performance of the combined structure of steel pipe and steel slag powder in ultra-high-performance concrete via a pure bending test and a finite element simulation [18]. Wang et al investigated the strength and failure characteristics of silty mudstone using different stress paths through triaxial unloading tests [19].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…Yang et al evaluated the effect of the number of drains per pile and the orientation of the drains relative to the direction of shaking [17]. Tang et al studied the flexural performance of the combined structure of steel pipe and steel slag powder in ultra-high-performance concrete via a pure bending test and a finite element simulation [18]. Wang et al investigated the strength and failure characteristics of silty mudstone using different stress paths through triaxial unloading tests [19].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…The results indicated that the method of filling the CFST beams with concrete increased the structural performance of the structure. Tang et al [15] conducted an experimental and analytical analysis of the flexural performance of CFT structures considering the diameter of the steel tube and the ratio of in-filled steel-slag micropowder ultra-high-performance concrete (UHPC). In this study, the load-deflection relationship according to the filling ratio of concrete was analyzed through the FEA model in a parametric study.…”
Section: Introductionmentioning
confidence: 99%